(untitled) (Medico Legal Update, 2021)
Optimize the development of children in NTB Province, the NTB golden generation program was launched. One of the efforts made to create a golden generation is by giving exclusive breastfeeding. Exclusive breastfeeding coverage in North Lombok Regency decreased from 73.94% to 45.50%. Breastfeeding failure is usually caused by improper technique and position. This study aimed to determine the effect of the demonstration of the correct breastfeeding technique on infant weight. This type of research is preexperimental with one group pre-post test design. The population was all breastfeeding mothers and babies at the Posyandu in Jenggala Village. The sampling technique used purposive sampling. The number of samples was 32 people. Data analysis using paired sample t-test. The results showed that the baby’s weight before the demonstration of the breastfeeding technique was most appropriate, namely 90.6%, and the bodyweight after the demonstration of the breastfeeding technique was mostly by it, namely 100.0%. The results of the paired sample t-test obtained a value of 5.568 with a p-value of 0.000 (p <0.05), this indicates that there is an effect of the correct method of breastfeeding demonstration technique with the baby’s weight. This study concludes that underweight babies can be increased by providing the correct breastfeeding technique so that the baby’s weight increases.